Phytoremediation and mathematical model for domestic wastewater by Chlorella vulgaris - Mamun, Abdullah Al; Amid, Azura; Abd. Karim, Imtinan; Alam, Md Zahangir; Sayem, S.M. (American-Eurasian Network for Scientific Information (AENSI), 2015)
Nutrient pollution of aquatic environment through disposal of industrial and domestic wastewater poses serious problems for reusing surface water and aquatic life. This study reports the feasibility and kinetics of Chlorella vulgaris in removing chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) for protection of surface water resources. The microalgal strain was cultured in shake flasks with wastewater and artificial light. Maximum biomass (200 mg/L) was achieved within four days, whereas maximum removal of TN, TP and COD was found to be 77.8%, 86.1% and 77.8%, respectively. Optimum detention period for phytoremediation was varied from 9 to 13 days. Phytoremediation performances of C. vulgaris were simulated through mathematical modeling, revealing kinetic coefficient values of 0.137, 0.171 and 0.13 for TN, TP and COD respectively. Based on laboratory scale study under controlled environment, it can be concluded that C. vulgaris has potential to reduce nutrient contents of wastewater.